Analisis Penerapan Psak No 16 Terhadap Perlakuan Aset Tetap: (Studi PT Berkah Ela Pratama) - Vanni Putri Sukma Wibawani; Ririn Qori Anna; Via Rahmawati; Reza Amelia Putri; Endang Kartini Panggiarti (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This research aims to determine the analysis of the application of PSAK NO 16 to the treatment of fixed assets. This research uses a literature review method which does not involve collecting primary data through direct observation or experimentation but focuses on previously existing studies. The results of this research indicate that PT Berkah Ela Pratama has conveyed that the overall financial report is in accordance with the requirements and standards for the Implementation of Financial Accounting Standards (PSAK) as the basis for preparing and presenting the current year's financial reports. PT Berkah Ela Pratama provides users with a fair representation of relevant and reliable financial information as required by standards, emphasizing full disclosure. Therefore, for most users, the purpose of viewing financial reports is still fulfilled.